Mabbakkang Tradition and Its’ Effects on Health of Villagers of Bacu Bacu Pujananting Barru: A Qualitative Study - Fiqriatul Hidayah; Nuurhidayat Jafar; Silvia Malasari (Indonesian Contemporary Nursing Journal, 2018)
Introduction: Indonesia is an archipelago country that has a diversity of race, culture and customs. Not infrequently customs that are believed by some to be not only a positive impact, but sometimes have a negative impact, especially in health problems.To identify Mabbakkang indigenous phenomenon and its effect on the health of the communities in the District Bacu-Bacu, Pujananting Barru. Method: Type of studi isQualitative research (phenomenology) was performed on 9 participants who have experience in custom undergo Mabbakkang through interview techniques in-depth interviews and data were analyzed by thematic analysis the technique developed by Colaizzi. Result: This study resulted in 7 themes on a custom implementation Mabbakkang ie execution time, the implementation, a series of execution, people involved, dietary restrictions, reason, and the consequences of breaking taboos. Conclusions: This study shows that a custom implementation Mabbakkang is one tradition that is held each year as a condition for the perfection of a child-Bacu-Bacu village communities and give effect on the health of the communities in the District Bacu Bacu-Pujananting Barru if breaking taboos.